Business Pragmatics: Why are we being polite? - Cheng, R. (2015)
For many of those who were brought up to ‘say please and thank you’ and were taught to ‘hold the door for the person behind,’ politeness was a ‘compulsory component’ of what was once considered to be a good man’s character. In those days, attempting to be ‘polite merely on the surface’ could end up being scolded by one’s parents, if not being remonstrated or immediately looked down upon as hypocrites by peers or even by business partners. Yet today, politeness in business has become more of a forced phenomenon of mutual concession, a pragmatic means to an end, or even a new form of reciprocal comity resulting from the inevitable mutual co-existence and quests for sustainability of nations, let alone international trade and relations. But when did politeness escape from the self and evolved to become a business phenomenon? Could it be triggered by a series of trade related or historical events or was it simply naturally evolving? Did researchers notice this in the course of human history? What would be the next phase of business politeness research? In this paper, we shall attempt to look at business politeness from the historical perspective of global business trends (including trade, world population, etc.) starting with the early eighteenth century as well as study the possible implications, and hence its future developments.